シミュレーションに基づく絡み合い高分子のレオロジーに関する研究 - Takimoto, Jun-ichi (Nihon Reoroji Gakkaishi, 2016)
A slip-link model of entangled polymeric liquid and its applications are presented. The model includes the three major relaxation mechanisms of entangled polymers, i.e., reptation, contour length fluctuation and constraint renewal. It can predict various linear and nonlinear rheological properties of linear and star polymers. Especially, it can quantitatively predict, without any fitting parameters, the enhancement of the strain hardening of uniaxial elongational viscosity by an addition of small amount of a very high molecular weight component. The effect of dynamical tube dilation (DTD) is also correctly included. A new interpretation of DTD in the framework of the slip-link model is proposed.